About the Way of Life of Zahiriddin Muhammad Babur in His Creative Activity - Istamovna, Adizova Obodon; Hamidovna, Toirova Mavluda (European Journal of Life Safety and Stability (2660-9630), 2021)
This article is devoted to the ability of academic Aziz Kayumov to apply of using in comprehending historical novels. Content and linguistic peculiarities of the research are analyzed too.